2014
DOI: 10.1002/art.38764
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A Novel Application of Buccal Micronucleus Cytome Assay in Systemic Lupus Erythematosus: A Case–Control Study

Abstract: Objective. Systemic lupus erythematous (SLE) is a systemic autoimmune disease, and both genetic and environmental factors are implicated in its pathogenesis. The aim of this study was to assess cellular and nuclear morphology of SLE using a buccal micronucleus cytome assay.Methods. This study included 58 SLE patients and 58 healthy age-and sex-matched controls. Patients' baseline characteristics were recorded, and a buccal micronucleus cytome assay was used to measure cellular and nuclear abnormalities in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The MN assay, as marker of chromosome breakage and chromosome loss, has been envisaged as a promising candidate in this perspective. Consistently higher frequencies of MN in the lesion area compared with normal tissue (56,58,59) and in association with the histological grade of oral carcinomas (59) were observed in patients with cancer and preneoplastic diseases.…”
Section: Oral Cancer and Head And Neck Cancersupporting
confidence: 51%
See 1 more Smart Citation
“…The MN assay, as marker of chromosome breakage and chromosome loss, has been envisaged as a promising candidate in this perspective. Consistently higher frequencies of MN in the lesion area compared with normal tissue (56,58,59) and in association with the histological grade of oral carcinomas (59) were observed in patients with cancer and preneoplastic diseases.…”
Section: Oral Cancer and Head And Neck Cancersupporting
confidence: 51%
“…A total of 56 full-text articles were assessed for eligibility. Forty-two of them met the criteria to be included in the systematic review, while the remaining studies were excluded due to lack of control group (18, 51-53) of data about MN values(54)(55)(56) or because they report only results on treated patients(57) or not related to specific diseases(58). Five low-size studies on patients with different genetic diseases were not included in our review(13)(14)(15)(16)59) …”
mentioning
confidence: 99%
“…They analyzed the effect of CYC and the influence of CYP2D6 polymorphisms on MN formation in patients with SLE; they found that the genotoxicity is increased in patients with SLE after CYC boluses without an association with the CYP2D6 allele expression, which contributes to the idea that irrespective from treatments patients with AD exhibit higher MN formation when compared to healthy subjects. The most recent study in this field was published in 2014 by Al-Rawi et al [ 30 ]; after assessing nuclear morphology in 58 SLE patients and 58 healthy age- and sex-matched controls by the use of buccal micronucleus cytome assay, they proposed a score with a cutoff value of ≥4 that exhibited a high accuracy (93.1%), higher positive predictive value (98.1% at 50% pretest probability and 99.8% at 90% pretest probability), sensitivity of 87.9%, and specificity of 98.3% for the diagnosis of SLE. After these findings, they concluded that the buccal micronucleus cytome assay was a valid and easy way for clinicians to assess individuals at high risk for developing SLE, since a negative result in the total micronuclei count excluded a possible diagnosis of SLE with 98.9% confidence in a clinical setting in which the differential diagnosis of SLE was of low probability (10% pretest probability).…”
Section: Resultsmentioning
confidence: 99%
“…The results of our current study showed no significant difference in the mean values of MN frequency in patients with SLE (RG) versus healthy individuals (CG) ( P = 0.057). [ 22 ] The variation in our results could be attributed to the fact that patients were undergoing medical treatment before the start of the study, and therefore their SLEDAI scores were under control. Our study utilized SLEDAI scores for the categorization of patients because of its practicality and simplicity of use, making it easy to monitor disease status and treatment outcomes.…”
Section: Discussionmentioning
confidence: 97%